2014
DOI: 10.1038/oncsis.2014.2
|View full text |Cite|
|
Sign up to set email alerts
|

The essential role of TNIK gene amplification in gastric cancer growth

Abstract: Traf2- and Nck-interacting kinase (TNIK) is one of the germinal center kinase family members involved in cytoskeleton organization and neuronal dendrite extension. Emerging evidence supports that TNIK is essential for activation of WNT signaling pathway in colon cancer growth. To search for novel genetic aberrations that drive carcinogenesis, we performed microarray-based comparative hybridization assay for gene copy number variations in primary tumor samples. Our data showed that TNIK gene was amplified in 7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 16 publications
1
32
2
Order By: Relevance
“…For example, TNIK forms a complex with β-catenin and TCF-4 in colorectal cancer, only activating TCF-4 at the S154 residue, and then the phosphorylated TCF-4 recruits to the promoters of Wnt target genes. By contrast, Yu DH et al [8] demonstrated an oncogenic role of TNIK in gastric cancer independent of Wnt/β-catenin pathway. ShRNA-mediated TNIK silencing did not result in decreased expression of genes controlled by Wnt/β-catenin pathway, but in reduction of p-Akt and induction of LC3, suggesting the tumorigenic behavior of TNIK in gastric cancer in a manner of PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, TNIK forms a complex with β-catenin and TCF-4 in colorectal cancer, only activating TCF-4 at the S154 residue, and then the phosphorylated TCF-4 recruits to the promoters of Wnt target genes. By contrast, Yu DH et al [8] demonstrated an oncogenic role of TNIK in gastric cancer independent of Wnt/β-catenin pathway. ShRNA-mediated TNIK silencing did not result in decreased expression of genes controlled by Wnt/β-catenin pathway, but in reduction of p-Akt and induction of LC3, suggesting the tumorigenic behavior of TNIK in gastric cancer in a manner of PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 89%
“…SiRNA-mediated knockdown of TNIK inhibits tumor cell growth and migration and promotes apoptosis and autophagy in several tumor cell lines [7,8]. These studies revealed a crucial role of TNIK in the initiation and progression of gastric and colorectal cancer.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The antiproliferative activity was evaluated by using Hoechst and the propidium iodide staining assay (Yu et al, 2014). In brief, cells were seeded in a 96-well plate at 6 Â 10 3 cells/well 24 hours prior to treatment.…”
Section: Methodsmentioning
confidence: 99%
“…88 Since Novo Nordisk first set up its research and development center in Beijing in 1997, Roche, AstraZeneca, Novartis, GlaxoSmithKline, and Eli Lilly, to name a few, all have followed the lead and established their drug discovery presence in China, aimed at tapping the local talent pool and reducing development expenditure. Both original research (such as target validation, [89][90][91][92] lead generation, [93][94][95] and preclinical evaluation [96][97][98][99] ) and outsourcing projects are routinely performed in these centers. Obviously, their presence has raised the standard of research, disseminated expertise of invention, and trained a new pool of specialists, all extremely useful to China's endeavor for innovation.…”
Section: Academic Institutions Still Leading the Waymentioning
confidence: 99%